Instructor or Customer Service Representative?: Reflections on Teaching in a For-Profit College - Madden, Jaime (Radical Teacher, 2018)
Conversations about the state of higher education in the US are increasingly attuned to the predatory practices of for-profit colleges. The essay offers a critical retrospective engagement with my experience teaching at a for-profit institution of higher education. It provides a theorization of what I found to be a "customer service orientation"–a distinctive expectation the college has about how instructors interact with their students, as well as a skill instructors are asked to foster in students. After briefly outlining the institution’s spatial configuration and how that supports its customer service orientation, I focus on two aspects of the for-profit educational experience: 1) the classroom experience within a generic sociology course, where students and I worked against the customer service orientation; and 2) a close reading of a course textbook assigned to all incoming students, which reveals most clearly the dual operations of neoliberal individualism and a customer service orientation. The classroom scenes detailed in this essay depict the complex and calculated negotiations of teachers and students with academic capitalism.